(untitled) (Journal of Engineering and Health Sciences, 2022)
The internet of Things (IoT) is a new paradigm that has transformed the traditional way of life into a high-tech lifestyle. Smart cities, smart homes, pollution control, energy saving, smart transportation, smart industries are the changes caused by the IoT. Many important studies and researches have been done to improve technology through IoT. However, there are still many challenges and problems that need to be addressed to achieve the full potential of the IoT. These challenges and problems must be considered from various aspects of IoT such as applications, challenges, possible technologies, social and environmental impacts etc. The main purpose of this review article is to provide a detailed discussion from a technological and social perspective. This article discusses the various challenges and key issues of the IoT, architecture and important application domains. The article also showcases the available literature and describes their contributions in various aspects of the IoT. Moreover, the importance of big data and its analysis with respect to IoT has been discussed. This article will help researchers to understand the IoT and its application to the real world